Applying of informational model of nutrition ration calculation for compensation of energy losses of the Ukrainian Armed Forces servicemen - Yu.M. Deputat; M.P. Gulich; V.L. Savytskyi; O.M. Ivanko; Yo.R. Levit; O.V. Bogomolets (Medičnì Perspektivi, 2021)
The article is devoted to the research of the problem of compensation of energy losses of servicemen doing  qualification course of the UAF Special Operations Forces as well as development of the method of promp response of the officials of food service on changing of energy losses of servicemen on different phases of qualification course by corresponding correction of their daily nutrition ration. The aim of work was directed for development and substantiation of informational model of nutrition ration calculation for compensation of energy losses of the Ukrainian Armed Forces servicemen. Time and tabular method of energy losses calculations, calculations of ration composition, instrumental estimations, laboratory and statistics assessments were used as methods of research. Calculations of informational model were done in Microsoft Excel 2007 functional environment. The description of informational polyparametrical model of the computational system of nutrients composition and energy value of servicemen daily nutrition ration depending on revealed energy losses doing qualification course of UAF Special Operations Forces has been presented. The model is meant for operative calculations of nutrients composition and energy value for compensation of energy losses of corresponding servicemen doing different phases of qualification course. Informational model got approval and was implemented in the UAF Special Operations Forces activities.